Pautas de control de la disciplina para prevenir las conductas disruptivas dentro del aula de clase, dirigido a niños y niñas de sexto año de educación básica de la escuela José Ingenieros, 2017-2018 - Quezada Campoverde, Daniela Estefania (2018)
The present thesis titled GUIDELINES OF DISCIPLINARY CONTROL TO PREVENT DISRUPTIVE BEHAVIOR WITHIN THE CLASSROOM, ADDRESSED TO BOYS AND GIRLS IN THE SIXTH YEAR OF BASIC EDUCATION AT THE SCHOOL OF JOSÉ INGENIEROS, 2017-2018, has the objective to implement guidelines of disciplinary control to prevent disruptive behavior. The study is descriptive, has a pre-experimental design and is cross-sectional; the methods used were the inductive, deductive, scientific, synthetic, analytical and statistical. The evaluation questionnaire was applied to the disciplinary problem of the school: the type of disruption and anti-social behavior of Fidel Navarro García, in a sample of 22 students. The workshop modality was used for the execution of the educational intervention program as one of the solution alternatives. The results (pretest) considering the significant levels (high and average) were: disruptive behaviors towards homework (81.82%), disruptions to facilities and materials (68.18%), disruptive attitude towards their classmates (77.27%) and disruptions to the teacher (63.64%); after the application of the proposal the levels of each factor decreased considerably placing higher percentages in the low level. It is concluded that students' disruptive behaviors are high in relation to schoolwork, facilities, and materials, and through the intervention process on disciplinary control guidelines, these disruptive behaviors decreased to low levels.